Beyond Big Data: the Dual Mediation of Perceived Personalization and Customer Engagement in the Analytics Loyalty Link within Digital Markets - Purwanto, Nuri; Amelia, Amelia; Irawan, Nico (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Digital marketplaces leverage Big Data Analytics (BDA) to understand customer behavior, but the mechanisms by which BDA forms loyalty remain unclear, particularly through personalized perceptions and customer engagement; whereas competition and low switching costs make loyalty difficult to maintain. Purpose: The purpose of this study is to examine the effect of BDA capabilities on customer loyalty and the dual mediating role of perceived personalization (PP) and customer engagement (CE) in the digital marketplace.Design/methodology/approach: A cross-sectional quantitative study on 300 marketplace users in Surabaya (≥17 years; ≥3 transactions/6 months) with purposive sampling. Data were collected via a Likert scale online questionnaire (items adapted from the literature) and analyzed with PLS-SEM (SmartPLS 4.0) and bootstrapping for mediation testsFindings/Result: The results show that the use of big data analytics in digital marketplaces is able to strengthen customer loyalty through two main channels. First, as the platform gets better at processing and utilizing customer data, customers increasingly feel that there are services that suit their personal needs, such as relevant product recommendations, targeted offers, and a shopping experience that feels "understood". Second, the use of big data analytics also encourages customers to be more involved, for example more actively interacting with platform features, providing responses, and building more intense relationships with the marketplace. Furthermore, both customers’ perceived sense of personalization and increased engagement have been shown to contribute to loyalty, which can be seen in the tendency of customers to continue using the same marketplace, make repeat purchases, and recommend them to others. These findings also confirm that big data analytics not only directly affect loyalty, but primarily work by improving the personalized customer experience and encouraging active engagement, both through individual channels and as a series of interconnected processes.Conclusion: Big data analytics capabilities are an important determinant in building loyalty in the digital marketplace, but the benefits are strongest when big data analytics is realized as an experience that feels personalized and triggers active customer engagement. Based on these findings, companies need to integrate analytics investments with relevant personalization designs and ongoing engagement strategies to build long-term loyalty. Originality/value (State of the art): This study proposes an integrated dual/sequential mediation model that combines resource-based theory and customer engagement theory to explain the psychological behavioral pathways of loyalty formation in the Indonesian digital market.Keywords:  big data analytics, perceived personalization, customer engagement, customer loyalty, digital market